2023
DOI: 10.3390/diseases11010051
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio as a Predictor of Postoperative Outcomes in Traumatic Brain Injury: A Systematic Review and Meta-Analysis

Abstract: (1) Introduction: Traumatic brain injury (TBI) is a leading cause of injury and mortality worldwide, carrying an estimated cost of $38 billion in the United States alone. Neutrophil to lymphocyte ratio (NLR) has been investigated as a standardized biomarker that can be used to predict outcomes of TBI. The aim of this review was to determine the prognostic utility of NLR among patients admitted for TBI. (2) Methods: A literature search was conducted in PubMed, Scopus, and Web of Science in November 2022 to retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…[ 17 ] The NLR is a marker of inflammation and is used in conjunction with other inflammatory markers to determine the severity of the body condition in some inflammatory diseases. [ 18 , 19 ] NLR was significantly higher in patients with severe pneumonia and acute respiratory distress syndrome compared to controls. [ 20 ] In our research, we found that the NLR in the BPD group was higher than that in the non-BPD group at birth.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The NLR is a marker of inflammation and is used in conjunction with other inflammatory markers to determine the severity of the body condition in some inflammatory diseases. [ 18 , 19 ] NLR was significantly higher in patients with severe pneumonia and acute respiratory distress syndrome compared to controls. [ 20 ] In our research, we found that the NLR in the BPD group was higher than that in the non-BPD group at birth.…”
Section: Discussionmentioning
confidence: 99%